2020
DOI: 10.1038/s41467-020-17297-z
|View full text |Cite
|
Sign up to set email alerts
|

Low-voltage 2D materials-based printed field-effect transistors for integrated digital and analog electronics on paper

Abstract: Paper is the ideal substrate for the development of flexible and environmentally sustainable ubiquitous electronic systems, which, combined with two-dimensional materials, could be exploited in many Internet-of-Things applications, ranging from wearable electronics to smart packaging. Here we report high-performance MoS 2 field-effect transistors on paper fabricated with a "channel array" approach, combining the advantages of two large-area techniques: chemical vapor deposition and inkjet-printing. The first a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
111
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(132 citation statements)
references
References 65 publications
2
111
0
Order By: Relevance
“…However, the current development stage of printed RFID tags is still not sufficient to enable real-world applications [ 70 ]. Despite the availability of printed organic transistors with carrier mobilities over 1 cm 2 V −1 s −1 and switching speed in the MHz range [ 71 ], silicon electronics strongly outperform printed electronics in terms of carrier mobilities and switching speeds, as shown in Table 5 . However, printed electronics still provide interesting characteristics related to manufacturing on soft substrates in large areas.…”
Section: Chipless Sensorsmentioning
confidence: 99%
“…However, the current development stage of printed RFID tags is still not sufficient to enable real-world applications [ 70 ]. Despite the availability of printed organic transistors with carrier mobilities over 1 cm 2 V −1 s −1 and switching speed in the MHz range [ 71 ], silicon electronics strongly outperform printed electronics in terms of carrier mobilities and switching speeds, as shown in Table 5 . However, printed electronics still provide interesting characteristics related to manufacturing on soft substrates in large areas.…”
Section: Chipless Sensorsmentioning
confidence: 99%
“…[ 20 ] More recently, the present authors demonstrated low‐voltage and transfer printed MoS 2 FETs on paper in a channel array configuration, with inkjet‐printed hexagonal boron nitride (hBN) gate dielectric and Ag contacts. [ 21 ] These flexible devices exhibited good performance with average carrier mobility of 5.5 cm 2 V −1 s −1 (maximum of 25 cm 2 V −1 s −1 ) and on‐off current ratio of ≈ 10 4 over a statistics of 26 devices, and have been successfully used in digital and analog applications, such as high‐gain inverters, AND gates, and current mirrors. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…The combination between low cost (~ 0.1 €/m2), biodegradability and flexibility makes paper-based electronics very promising for applications like disposable wearable electronics and sensors. [1][2][3][4][5][6][7][8][9][10] However, the integration of novel electronic materials, like the van der Waals (vdW) materials family, on paper substrates is hampered by their fibrous structure that introduces a large surface roughness and liquidabsorption. For these reasons, standard device fabrication approaches, developed and optimized for the fabrication of devices on silicon substrates, cannot be directly used on paper substrates.…”
Section: Introductionmentioning
confidence: 99%